Inclination to pursue Veterans Health Administration for primary care practice: survey of medical residents - Henrikson, Nora B.; Moldestad, Megan; Maynard, Charles; Kaboli, Peter J.; Reddy, Ashok; Rinne, Seppo T.; Sanders, Karen M.; Sterling, Ryan A.; Wong, Edwin S. (Frontiers in Health Services, 2024)
IntroductionHealth systems like the Veterans Health Administration (VA) face challenges in recruiting and retaining a primary care physician workforce. This cross-sectional study of recent or current VA medical residents sought to identify determinants of intent to pursue primary care practice in VA after residency training.MethodsResidents were identified from administrative data between 2020 and 2021 and recruited via an emailed self-administered survey. Multivariable logistic regression, accounting for survey non-response, was applied to examine the association between intent to pursue VA practice and two sets of measures: VA training experiences and individual preferences for work conditions.ResultsOf 268 responses received, 141 (56%) of the sample reported inclination to consider VA employment post-residency. Experiences with training in VA were rated more positively in the VA-inclined group compared to the not-inclined group. In the multivariable model, intent to practice primary care was the strongest predictor (OR 4.04, p < 0001). Preceptors' modeling of work-life balance (OR 3.23, p = 0.009) and perceptions of quality of clinical staff and services (OR 2.64, p = 0.004), ability to get patients the care they need (OR 2.51, p = 0.017), and quality of patient care (OR 2.30, p = 0.075) were independent predictors of being in the VA inclined group.ConclusionOverall, we found that intent to practice primary care and the quality of VA training experiences are important determinants of inclination to consider VA for employment. These results provide an important perspective relevant to medical education, the hiring and retention of the United States (U.S). primary care workforce.